2011
DOI: 10.1158/0008-5472.can-10-0618
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Cell Microchimerism and Cancer: A Nexus of Reproduction, Immunology, and Tumor Biology

Abstract: Fetal cell microchimerism (FCM) is the persistence of fetal cells in the maternal circulation and organs following pregnancy. Proposed hypotheses about the function of fetal cells in the pathogenesis of maternal cancer include promotion of tumorigenesis, protection by providing immunosurveillance, and participation in tissue repair. To date, studies of FCM and cancer have been primarily descriptive and quantitative. More research is needed to understand the cellular phenotype of the microchimeric cells in mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…The potential of antibodies as targeting ligands transcends tumor detection purposes. Radiolabeled antibodies could be extremely useful for both radioimmunotherapy (RIT) and tumor monitoring during therapy 31, 32, 33. To evaluate the potential of the anti‐human B‐B4 monoclonal antibody to target the syndecan‐1 (CD138) antigen—correlated with poor prognosis and aggressive phenotypes in breast carcinoma—a preclinical study on TNBC xenograft mice was performed 31.…”
Section: Tnbc: Strategies For Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of antibodies as targeting ligands transcends tumor detection purposes. Radiolabeled antibodies could be extremely useful for both radioimmunotherapy (RIT) and tumor monitoring during therapy 31, 32, 33. To evaluate the potential of the anti‐human B‐B4 monoclonal antibody to target the syndecan‐1 (CD138) antigen—correlated with poor prognosis and aggressive phenotypes in breast carcinoma—a preclinical study on TNBC xenograft mice was performed 31.…”
Section: Tnbc: Strategies For Diagnosis and Treatmentmentioning
confidence: 99%
“…These results reinforced the relevance of the B‐B4 antibody for the diagnosis and treatment of metastatic TNBC. Scheltinga et al have monitored downregulation of the insulin‐like growth factor receptor‐1 (IGF‐1R) and VEGF expression in vivo in response to heat shock protein 90 (Hsp90) inhibition therapy using Zirconium‐89 ( 89 Zr)‐labeled MAB391 and bevacizumab for PET imaging 32, 33. These studies not only demonstrated the utility of 89 Zr‐labeled antibodies in the visualization of IGF‐1R and VEGF levels in vivo, but also showed their potential as biomarkers for drugs targeting IGF‐1R and VEGF expression.…”
Section: Tnbc: Strategies For Diagnosis and Treatmentmentioning
confidence: 99%
“…It may not distributed all over the body. This phenomenon has been termed microchimerism and describes the long-term existence of infective microorganisms in an organism (Kallenbach et al, 2011;Miech R.P., 2010). It is possible to explain this phenomenon by our hypothesis.…”
Section: Hypothesis: Regulation Of Cellular Physiological and Patho-pmentioning
confidence: 99%
“…Microchimerism is the co-existence of a small population of cells from genetically distinct individuals living within the body of another individual [1,2]. In humans, during pregnancy, cells traffic bi-directionally across the placental interface between fetus and mother and establish permanent residence, resulting in fetal or maternal microchimerism.…”
Section: Introductionmentioning
confidence: 99%
“…A persistent microchimeric state can also result from medical intervention, such as organ transplantation or blood transfusion [3]. Ultimately, the result is the persistence of minor cell populations that may play roles in the development of autoimmune disease and some cancers, reduction of risk of other cancers, and enhancement of engraftment rates following hematopoietic stem cell or organ transplantation with a reduction in graft vs host disease (GVHD) [1,4,5]. While significant epidemiological data supports differential risk for certain diseases between women with demonstrated fetal microchimerism and those without, the diseases are multifactorial in cause and often late to develop in life [4,6].…”
Section: Introductionmentioning
confidence: 99%